Registry report of structural and functional cardiac abnormalities diagnosed by echocardiography in an asymptomatic population. Issue 1090 (19th February 2016) - Missouris, Constantinos G; Okonko, Darlington O; Bharucha, Apurva; Al-Obaidi, Mohamed; Mandal, Amit K; Highett-Smith, Paul; Singer, Donald R J
Abstract: Background: The epidemiology of heart disease is changing, with rheumatic heart disease becoming less common but degenerative valve disorders, heart failure and atrial fibrillation (AF) increasing. Objective: We sought to determine the prevalence of structural cardiac abnormalities in the apparently symptom-free adult population within our prospective echocardiography (echo) registry. Methods: Our echo registry comprised echo studies and associated demographic and clinical data obtained prospectively from 362 consecutive asymptomatic subjects aged 50–74 years and without known heart disease referred between 2011 and 2012 from general practices in the South East of England. Results: 221 echo abnormalities were detected in 178 (49%) subjects (46% men; mean (±SD) age 63.9±9.2 years; 98% Caucasian). A major abnormality was detected in seven subjects: four had a large secundum atrial septal defect, one had critical aortic stenosis, one severe mitral regurgitation and one features of hypertrophic cardiomyopathy. Twelve subjects had left ventricular systolic dysfunction with an ejection fraction (EF) <50% (of whom 10 had EF <40%). Four subjects had AF. Minor echo abnormalities were evident in the remaining 171 (47%) subjects. Abnormalities were commoner in patients with cardiovascular risk factors or a history of cardiac disease than in those without (53% vs 38%). In multivariate analyses stratified by gender, for women, increased age (F=33.3, p<0.001) and systolic blood pressure (F=9.2, p=0.003) were associated with abnormal echo findings; for men, increased age (F=12.0, p<0.001) and lower cholesterol (F=4.2, p=0.042) predicted an increase in abnormal findings on echo. Conclusions: Unrecognised cardiac abnormalities are very common in middle-aged men and women with no overt symptoms. Echo offers the potential to identify the need for early intervention and treatment to improve cardiovascular outcomes.